Effect of selected cereal grains on in vitro bioaccessibility of isoflavones in soymilk - Ng, C. C.; Loh, Su Peng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Soymilk, which can be called as plant based “milk” is a favourite traditional beverage in Asian with various beneficial health protective effects due to the presence of isoflavones. Mixing cereal grains into soymilk to make a wholesome beverage for breakfast becomes popular. However, dietary factors may affect the bioaccessibility of isoflavones. The aim of this current work was to evaluate changes in the bioaccessibility of isoflavones in soymilk after mixing with selected cereal grains following in vitro gastrointestinal digestion. The samples were subjected to in vitro gastrointestinal digestion with its isoflavones content determined before and after simulated gastric digestion and intestinal digestion with dialysis membrane. Soymilk contained 1.80 ± 0.03 mg daidzein and 2.12 ± 0.08 mg genistein in 100 ml, while bioaccessibility of soymilk daidzein and genistein were 11.24 ± 0.46% and 5.09 ± 0.25% respectively. The addition of cereal grains except barley in soymilk showed significant reduction (p<0.05) in bioaccessibility of isoflavones. Dietary fiber content, especially the insoluble fiber of cereal grains was related to the reduction of bioaccessibility of isoflavones by its entrapping affinity of isoflavones and viscosity effect in the gut. The higher the dietary fiber added into the soymilk, the lower the bioaccessibility of isoflavones in soymilk.